2018
DOI: 10.4025/cienccuidsaude.v17i1.40666
|View full text |Cite
|
Sign up to set email alerts
|

<b> Conhecimento dos profissionais que realizam pré-natal na atenção básica sobre o manejo da sífilis / Knowledge of professionals who do prenatal in the basic attention on the management of syphilis<b>

Abstract: O objetivo foi identificar o conhecimento dos profissionais do pré-natal sobre o manejo da sífilis gestacionalna atenção primária. Estudo transversal, descritivo, de natureza quantitativa, realizado com 43 profissionais. A coleta realizou-se entre julho e agosto de 2017, utilizando-se um questionário autoaplicado, elaborado com base nos protocolos do Ministério da Saúde para o manejo de sífilis gestacional. Os dados foram digitados e tabulados no Microsoft Excel 2010®, e analisados no software Statistical Pack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
11

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 5 publications
0
4
0
11
Order By: Relevance
“… 12 , 18 These data further reinforced the importance of diagnosis, access to treatment, and knowledge of health professionals in managing the disease in order to take effective action. 19 It is worth highlighting the need for training of the neonatal care team because some children were not tested at birth and others did not receive adequate treatment.…”
Section: Discussionmentioning
confidence: 99%
“… 12 , 18 These data further reinforced the importance of diagnosis, access to treatment, and knowledge of health professionals in managing the disease in order to take effective action. 19 It is worth highlighting the need for training of the neonatal care team because some children were not tested at birth and others did not receive adequate treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Distinguishing between stages is extremely important because treatment varies according to the stage of the disease. In addition, the same study showed that some of the professionals interviewed could not distinguish between treponemal tests (which detect specific antibodies to Treponema pallidum antigens) and non-treponemal tests (which detect non-specific antibodies to the bacteria) recommended by the Ministry of Health (12) . It is crucial to emphasize that health professionals should be adequately trained to provide effective reception and qualified listening to patients, thus establishing a bond with users.…”
Section: Discussionmentioning
confidence: 99%
“…A survey showed that 4.7% of participating healthcare professionals did not recognize congenital syphilis as a disease requiring reporting. This finding is worrisome because it has been included in the National List of Diseases, Conditions, and Public Health Events to be reported since 1986, and yet some professionals are not aware of this obligation, which favors the underreporting of the disease (12) . In the same vein, a study of the knowledge of syphilis management among professionals providing antenatal care in primary care settings found that they still have practices that contradict protocols, such as inadequate treatment, which contribute to the ongoing transmission of the infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A sífilis é uma Infecção Sexualmente Transmissível (IST), ocasionada pela dispersão do treponema pallidum na corrente sanguínea, sua contaminação ocorre por meio da relação sexual desprotegida, por via transplacentária e transfusão sanguínea. Representando um agravo na saúde pública, recebendo ênfase no cenário mundial com gradativo aumento no número de casos dos Gabriella Hellen Araújo de Oliveira, Nair Aires Santos, Carla Michelle Rodrigues Abreu, Ellen Rose Sousa Santos, Paulo Vinicius Marinho Ferreira, Josafá Barbosa Marins, Dayanne da Silva Freitas ____________________________________________________________________________ últimos anos, ainda que seja uma patologia evitável, com protocolos de prevenção, diagnóstico e tratamento 1 Segundo a Organização Mundial da Saúde (OMS), em 2016, possuíam aproximadamente 661 mil casos de sífilis congênita no mundo, procedendo mais de 200 mil natimortos e mortes neonatais². No Brasil, no período de 2011 a 2021, foram notificados 1.035.942 casos de sífilis adquirida, 466.584 casos de sífilis em gestantes, 221.600 casos de sífilis congênita e 2.064 óbitos por sífilis congênita.…”
Section: Introductionunclassified